An analysis of regional economic vulnerability through the lens of tourism dependence: The case of Spain. - Ortega-Aguaza, Bienvenido; Ribeiro, Manuel Alector (My University, 2023)
The main aim of this piece of work is to provide evidence of the existence of regions in Spain in which the excessive dependence on tourism is conditioning their long-term economic development possibilities, placing their economies in a position of economic vulnerability. To our knowledge, this will be the first attempt to analyse the relationship between dependence on tourism and economic vulnerability in Spain. Previously, Watson and Deller (2022) studied how dependency on tourism influences regional economic resiliency using US county-level data. Thus, in this study, attention will be paid to the relationship between economic dependence on tourism and economic vulnerability in Spanish tourist regions in the two most recent periods of recession: the ‘Great Recession’ of 2008 and the initial effects of the COVID-19 pandemic in 2020. With this aim, we will first conceptualise and measure regional economic vulnerability/resilience following the works of Briguglio et al. (2009) and Ringwood et al. (2019). Then an index of regional dependence on tourism will be developed in order to have a single tourism dependence indicator to be associated with differences in vulnerability/resilience regional scores previously calculated. In this regard, particular attention will be paid to the influence of differences in the portfolio of visitors on the levels of resilience of regional economies.
Keywords: Turismo - Aspectos económicos - España; Economic dependence on tourism; Economic vulnerability/resilience